Design of modern highway bridges - Taly, Narendra (Mc Graw Hill, 1998)
This text provides an introduction to the theory and practice of designing modern highway bridge superstructures. Beginning with the history of bridges, it describes various types of bridge superstructures, materials of construction, bridge loadings, and analysis techniques for various types.